Women’s empowerment through small-scale dairy farming in Bangladesh: a study on some selected areas of Mymensingh district (Asian-Australasian Journal of Food Safety and Security, 2019)
The study was designed to explore the women’s empowerment through small-scale dairy farming in Bangladesh. Small-scale dairy farm owners constituted the population of the present study. Among the population, the households who were actively engaged in dairy farming activities more than one year in the selected area of Mymensingh district, they were considered as the sample unit. For data collection, 50 households from the sample unit were randomly selected for interview. Simple percentages were calculated to show the frequency distribution at different categories of variables. Through small-scale dairy farming, rural women were able to increase their confidence and decision-making power with regard to their household and personal care and experienced increased self-esteem, expansion of their social circles, and ultimately enhanced empowerment through the breakdown of traditional socio-cultural norms. Thus, the expansion of small-scale dairy farming in other rural areas of Bangladesh is likely to contribute to the empowerment of more rural women.Asian Australas. J. Food Saf. Secur. 2019, 3(2), 85-95